2002
DOI: 10.1038/ng1015
|View full text |Cite
|
Sign up to set email alerts
|

Core-binding factor β interacts with Runx2 and is required for skeletal development

Abstract: Core-binding factor beta (CBFbeta, also called polyomavirus enhancer binding protein 2beta (PEBP2B)) is associated with an inversion of chromosome 16 and is associated with acute myeloid leukemia in humans. CBFbeta forms a heterodimer with RUNX1 (runt-related transcription factor 1), which has a DNA binding domain homologous to the pair-rule protein runt in Drosophila melanogaster. Both RUNX1 and CBFbeta are essential for hematopoiesis. Haploinsufficiency of another runt-related protein, RUNX2 (also called CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
221
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(227 citation statements)
references
References 31 publications
6
221
0
Order By: Relevance
“…Some mutations of Cbfa1 abolish its DNA binding activity (Lee et al, 1997;Zhou et al, 1999) and others disturb the association of Cbfa1 to its binding partners, including Smads (Xie et al, 2000). It was found that several Cbfa1-binding proteins such as retinoblastoma protein (pRb) (Thomas et al, 2001), p204 (Liu et al, 2005), and Core binding factor ␤ ( Kundu et al, 2002;Yoshida et al, 2002) may also play critical roles in bone development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mutations of Cbfa1 abolish its DNA binding activity (Lee et al, 1997;Zhou et al, 1999) and others disturb the association of Cbfa1 to its binding partners, including Smads (Xie et al, 2000). It was found that several Cbfa1-binding proteins such as retinoblastoma protein (pRb) (Thomas et al, 2001), p204 (Liu et al, 2005), and Core binding factor ␤ ( Kundu et al, 2002;Yoshida et al, 2002) may also play critical roles in bone development.…”
Section: Introductionmentioning
confidence: 99%
“…Some mutations of Cbfa1 abolish its DNA binding activity (Lee et al, 1997;Zhou et al, 1999) and others disturb the association of Cbfa1 to its binding partners, including Smads (Xie et al, 2000). It was found that several Cbfa1-binding proteins such as retinoblastoma protein (pRb) (Thomas et al, 2001), p204 (Liu et al, 2005), and Core binding factor ␤ ( Kundu et al, 2002;Yoshida et al, 2002) may also play critical roles in bone development.Inhibitor of differentiation (Id) proteins belong to the helix-loop-helix (HLH) family. Id proteins function as global regulators of gene expression during cell growth and differentiation (reviewed in Ruzinova and Benezra, 2003;Wong et al, 2004).…”
mentioning
confidence: 99%
“…Osteoblast differentiation and maturation are crucial events in the formation of new bone and determination of bone quality (Nakashima et al, 2002;Yoshida et al, 2002;Komori, 2010). Bone formation begins with the differentiation of osteoblasts from pluripotent mesenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…
Abbreviations used in this paper: CT, computed tomography; FACIT, fibrilassociated collagen with interrupted triple helices; HA, hydroxyapatite; H&E, hematoxylin and eosin; HU, Hounsfield unit; shRNA, short hairpin RNA; TMDn, tissue mineral density; TRAP, tartrate resistance acid phosphatase.
IntroductionOsteoblast differentiation and maturation are crucial events in the formation of new bone and determination of bone quality (Nakashima et al, 2002;Yoshida et al, 2002;Komori, 2010). Bone formation begins with the differentiation of osteoblasts from pluripotent mesenchymal cells.
…”
mentioning
confidence: 99%
“…The free RHD exists in a conformation in which affinity for DNA is nonoptimal, and CBF␤ binding to the RHD triggers a switch in the RHD structure that stabilizes it in a conformation for sustained DNA binding (13). CBF␤ is essential for Runx protein function because a homozygous mutation of CBF␤ results in a complete lack of fetal liver hematopoiesis (1,2) and severely defective bone formation (14,15).…”
mentioning
confidence: 99%